2016
DOI: 10.1111/cbdd.12790
|View full text |Cite
|
Sign up to set email alerts
|

Design of peptides as inhibitors of human papillomavirus 16 transcriptional regulator E1–E2

Abstract: Human papillomavirus 16 (HPV 16) is a DNA virus that is capable of infecting humans and causing cervical cancer. HPV16 E2 plays an important role in viral gene regulation. This work aims to predict the binding conformations and interactions between the dodecapeptides and HPV16 E2 as well as to design novel peptide inhibitors that are capable of binding to HPV16 E2 and disrupt the transcriptional regulator E1-E2 complex formation, using computational protein design techniques. Based on previously reported pepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 40 publications
0
3
0
1
Order By: Relevance
“…Previous studies have shown that E1 protein is necessary for HPV replication. On the transcription level, E1 can bind to upstream regulatory sequence of HPV to promote the expression of HPV E6 and E7 oncogenes [ 14 , 15 ]. Some scholars demonstrated that E1 participated in the early stage of carcinogenesis and can activate specific cytotoxic T cell responses [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that E1 protein is necessary for HPV replication. On the transcription level, E1 can bind to upstream regulatory sequence of HPV to promote the expression of HPV E6 and E7 oncogenes [ 14 , 15 ]. Some scholars demonstrated that E1 participated in the early stage of carcinogenesis and can activate specific cytotoxic T cell responses [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Disruption of episome maintenance can deregulate many aspects of the viral life cycle, including gene expression, DNA replication, and genome segregation. Several efforts to inhibit EMPs have been explored, including inhibitor assays of the LANA histone interaction domain [109], small-molecule inhibitors of the EBNA1 DNA-binding domain [110][111][112], and peptide inhibitors of E2 functions [113,114]. CRISPR/CAS9 genome editing of KSHV LANA [115], or EBV OriP [116,117] can reduce or eliminate viral episomes in cell culture models.…”
Section: Discussionmentioning
confidence: 99%
“…Binding affinities obtained for designed peptides and protein E2 of HPV16 recombinant were in good agreement with experimental results. Four peptides were the more efficient inhibitors of E1-E2 complex, and they could be used for suppression of HPV replication [55].…”
Section: Other Labs' Approachmentioning
confidence: 99%